Local Government and Efforts to Build Inclusivity of Community-Based Environmental Policies - I Wayan Astawa; I Komang Erik Arnata Wijaya (Indonesian Journal of Accounting and Financial Technology, 2025)
This study analyzes how the Denpasar City government builds community-based environmental policy inclusivity, focusing on public participation mechanisms, implementation challenges, and collaborative strategies. Using a Participatory Action Research approach—through participatory observation, in-depth interviews with eleven key informants, focus group discussions, and policy document analysis—the findings reveal persistent obstacles, including limited cross-sector coordination, restricted public access to deliberative spaces, and a dominant top-down policymaking approach. Nonetheless, community-based collaboration models, strengthened local institutional capacities, and the integration of local wisdom enhance policy legitimacy and effectiveness. The study contributes to participation-based environmental governance theory and offers practical recommendations for developing inclusive, sustainable, and community-responsive environmental policies at the local government level.